2019
DOI: 10.28945/4461
|View full text |Cite
|
Sign up to set email alerts
|

Technology Support, Social Support, Academic Support, Service Support, and Student Satisfaction

Abstract: Aim/Purpose: The study aimed to investigate the influence of technology support, social support, academic support, and service support on student satisfaction and their relationships in private and state universities. Background: Coherent support between students, teachers, and management is usually extended beyond classroom scheduling and space. This support has a positive significant influence on student satisfaction, which may influence students’ academic, behavioral, emotional and social development. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 51 publications
0
2
0
1
Order By: Relevance
“…Academic support has a positive and significant impact on learning satisfaction. The existing literature review [91][92][93] found that academic support has enhanced a high level of students' learning satisfaction. Overall, the results of SEM reveal that conceptual model to explore key consequences and antecedents of students' study commitment to online learning are explained by various theoretical backgrounds, including social learning theory, self-efficacy theory, social identity theory, and social cognitive theory.…”
Section: Interaction Of Study Commitment Of Students During Online Le...mentioning
confidence: 99%
“…Academic support has a positive and significant impact on learning satisfaction. The existing literature review [91][92][93] found that academic support has enhanced a high level of students' learning satisfaction. Overall, the results of SEM reveal that conceptual model to explore key consequences and antecedents of students' study commitment to online learning are explained by various theoretical backgrounds, including social learning theory, self-efficacy theory, social identity theory, and social cognitive theory.…”
Section: Interaction Of Study Commitment Of Students During Online Le...mentioning
confidence: 99%
“…Namun untuk negara berkembang seperti Indonesia, dimana sektor Edtech merupakan sektor yang baru berkembang dalam beberapa tahun terakhir, diperlukan sebuah kondisi yang membangun pengguna untuk dapat mendukung penggunaan platform teknologi dalam proses pembelajaran di dalam Edtech. Sehingga dibutuhkan dukungan informasi dan sumber daya dari lingkungan pengguna untuk mendukung penggunaan dan adaptasi teknologi yang akan digunakan dalam proses pembelajaran [19], [20].…”
Section: Pendahuluanunclassified
“…Participants recommended the amplification of institutional support to make the learning environment conducive and engaging. Competitive advantages are achieved when the institution fulfills the students' satisfaction by meeting their demands like sufficient facilities and equipment and strengthening students' social integration by reaching out to other institutions and establishing a connection (Kakada et al, 2019).…”
Section: Theme 7: Amplify Institutional Support and External Collabor...mentioning
confidence: 99%